Analysis of Public Sector Financial Reports at the Bantaeng Regency National Land Agency (BPN) - Nurhidayah, Nurhidayah; Wahyuni, Wahyuni; Nurul Fuada; Ismail Badollahi; Alam Nursandi (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is to determine the results of the performance and financial management of the Bantaeng Regency National Land Agency (BPN) in the 2017-2021 period. This research is a type of quantitative research with a descriptive approach. The data collection technique is carried out by direct observation and documentation, so that financial report data for 2017-2021 is obtained. With data analysis techniques using financial ratios. The results of financial report analysis research based on the harmony analysis method show that in 2017-2021 the average percentage value was 90%, which is said to be not good. The analysis of spending variances is generally said to be good, because it does not exceed what was budgeted. The spending efficiency ratio is said to be less efficient because the spending budget is too high. The current ratio shows that from 2017 to 2021 it is said to be good. Because the percentage value is not less than 1%.